Meningkatkan Mutu Pendidikan Di Pesantren - Iqbal Fahri (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2020)
Abstract: Islamic boarding schools are the oldest Islamic education institutions in Indonesia that have religious goals, but there are pesantren that are considered not able to actualize these pesantren for the development of the times. In this paper, the authors use the research library as a method. This paper aims to describe the leadership of the kiai in improving the quality of education in pesanten in the current era, how the leadership model and also how the role of a kiai in improving the quality of education in pesantren. The kiai kiai have been able to strengthen the existence of the pesantren institution, largely succeeding in producing santri who have morality and are also capable in religious matters, but are less able to respond and are accommodating to the needs of the times. With the leadership model of a kiai who is able to read the development of the times will give birth and develop a good quality pesantren education. Keywords: Leadership , kiai, pesantren.